Helping children of rural, methamphetamine-involved families : the case of rural Illinois - Haight, Wendy L., 1958- (New York ; Oxford : Oxford University Press, 2009)
This text follows a case in rural Illinois, where in the mid-1990s methamphetamine production & misuse became a big problem &, as a result, child welfare professionals saw an influx of children whose parents were involved with the drug. This is an account of the problems the children faced, and of the efforts to help them.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Methamphetamine abuse -- Illinois; Drug addicts -- Family relationships -- Illinois; Rural children -- Illinois -- Social conditions; Rural children -- Services for -- Illinois; Children of drug addicts -- Illinois -- Social conditions; Methamphetamine -- Illinois